1993
DOI: 10.1007/bf01581659
|View full text |Cite
|
Sign up to set email alerts
|

Black-white regional migration and the impact of education: a multinomial logit analysis

Abstract: "This study investigates the demographic determinants of regional migration within the United States for the periods 1965-70 and 1975-80.... Data used in the analysis are drawn from the United States census public-use microdata samples. Strong evidence is provided demonstrating that an individual's choice of destination region differs by race and that educational attainment has a significant impact on racial differences in the direction of regional migration. Moreover, racial selectivity and the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Given the differential historical migration patterns for black and white people, 22,23 race-stratified analyses were conducted, adjusting for age and sex. Because of missing stroke data due to ongoing adjudication and differential retrieval of medical records, we applied multiple imputation techniques to classify potential stroke events using a logistic function predicting the likelihood that an attempted record retrieval would result in an adjudicated stroke.…”
Section: 18mentioning
confidence: 99%
“…Given the differential historical migration patterns for black and white people, 22,23 race-stratified analyses were conducted, adjusting for age and sex. Because of missing stroke data due to ongoing adjudication and differential retrieval of medical records, we applied multiple imputation techniques to classify potential stroke events using a logistic function predicting the likelihood that an attempted record retrieval would result in an adjudicated stroke.…”
Section: 18mentioning
confidence: 99%
“…However, in a certain context this is not true (Krieg 1993). The likelihood of being a migrant 4 Because we treat independent migrants as individuals who came from the same COGRP or PUMA in 1980 or 1990, there is a possibility of some having lived separately at the outset of either period.…”
Section: Independent Variables: Human Capital/life-cycle Factorsmentioning
confidence: 99%
“…However, this is not an unusual ®nding given that previous studies have found a higher propensity among women to migrate than among men, depending upon the various contexts. For example, Krieg (1993) reports that women's propensity to migrate is much stronger than men's towards the areas of the West and Northeast which are more urbanized. Highly urbanized areas, in general, provide a more favorable industrial environment (e.g., service, retail sales), which is generally thought to be more advantageous for women's employment (Isserman and Rephann 1993).…”
Section: Stayers (S)mentioning
confidence: 99%
“…We expect that the likelihood of migration and homeownership should increase with higher education. In general, the well-educated are more likely to make long-distance moves (Greenwood 1975;Krieg 1993).…”
Section: Independent Variablesmentioning
confidence: 99%